The Full Spectrum of Clinical Ethical Issues in Kidney Failure. Findings of a Systematic Qualitative Review. - Hannes Kahrass; Daniel Strech; Marcel Mertz (PLoS ONE)
Background When treating patients with kidney failure, unavoidable ethical issues often arise. Current clinical practice guidelines some of them, but lack comprehensive information about the full range of relevant ethical issues in kidney failure. A systematic literature review of such ethical issues supports medical professionalism in nephrology, and offers a solid evidential base for efforts that aim to improve ethical conduct in health care. Aim To identify the full spectrum of clinical ethical issues that can arise for patients with kidney failure in a systematic and transparent manner. Method A systematic review in Medline (publications in English or German between 2000 and 2014) and Google Books (with no restrictions) was conducted. Ethical issues were identified by qualitative text analysis and normative analysis. Results The literature review retrieved 106 references that together mentioned 27 ethical issues in clinical care of kidney failure. This set of ethical issues was structured into a matrix consisting of seven major categories and further first and second-order categories. Conclusions The systematically-derived matrix helps raise awareness and understanding of the complexity of ethical issues in kidney failure. It can be used to identify ethical issues that should be addressed in specific training programs for clinicians, clinical practice guidelines, or other types of policies dealing with kidney failure.